2012
DOI: 10.1093/infdis/jis305
|View full text |Cite
|
Sign up to set email alerts
|

CAPRISA 004 Tenofovir Microbicide Trial: No Impact of Tenofovir Gel on the HIV Transmission Bottleneck

Abstract: Alterations of the genital mucosal barrier may influence the number of viruses transmitted from a human immunodeficiency virus-infected source host to the newly infected individual. We used heteroduplex tracking assay and single-genome sequencing to investigate the effect of a tenofovir-based microbicide gel on the transmission bottleneck in women who seroconverted during the CAPRISA 004 microbicide trial. Seventy-seven percent (17 of 22; 95% confidence interval [CI], 56%-90%) of women in the tenofovir gel arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…In order to unravel whether the difference in VL in this study is a direct effect of PrEP, or due to the selection of two distinct cohorts after tenofovir gel exposure, further studies are underway. We have already established that the diversity, fitness and resistance pattern of the transmitted virus, as well as T cell responses 1619 were not adversely affected by 1% tenofovir gel exposure, and are currently investigating whether a delay in the antibody response of women who used the tenofovir gel could have been a contributing mechanism to explain the difference in VLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to unravel whether the difference in VL in this study is a direct effect of PrEP, or due to the selection of two distinct cohorts after tenofovir gel exposure, further studies are underway. We have already established that the diversity, fitness and resistance pattern of the transmitted virus, as well as T cell responses 1619 were not adversely affected by 1% tenofovir gel exposure, and are currently investigating whether a delay in the antibody response of women who used the tenofovir gel could have been a contributing mechanism to explain the difference in VLs.…”
Section: Discussionmentioning
confidence: 99%
“…In the CAPRISA 004 1% tenofovir gel microbicide trial 5 , women who acquired HIV in the tenofovir and placebo arms were offered enrolment into the CAPRISA 002 Acute Infection cohort study 15 . Research on these women from acute HIV infection has already established that the diversity of the transmitting virus was similar between seroconvertors from the two arms 16 and tenofovir gel did not appear to select for viruses with enhanced fitness 17 . Interestingly, T cell responses were relatively preserved during early infection amongst women who were randomized to receive tenofovir gel but who seroconverted 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The drugs and delivery systems used must protect in the context of these factors. Indeed, this effect may have contributed to the observation in Centre for the AIDS Programme of Research in South Africa (CAPRISA) 004 that immune activation was associated with HIV acquisition, even among women using TFV gel (33). Another clear and related advantage of TDF over TFV is the potential for providing protection against HSV-2 acquisition and outbreaks because TDF is ∼100-fold more potent against HSV-2 (13).…”
Section: Significancementioning
confidence: 99%
“…We previously reported that TFV use did not alter the number of transmitted/founder variants identified in these women (53), nor did it select for transmitted drug resistance (54). However, higher VLs were observed in women who became infected in the TFV arm, raising concerns that TFV might have selected for the transmission of fitter variants (39), but our results provide no evidence to support this hypothesis, as viral infectivity was 2-fold lower in the TFV arm and the RCs did not differ between the trial arms.…”
Section: Figmentioning
confidence: 76%
“…Sequences were excluded if they contained Ͼ3 double peaks in the chromatogram or deletions Ͼ30 nucleotides long. To include plasma-derived Env V3V5 sequences that were already available for comparison (53), all other sequences were truncated to the V3V5 region. Sequences were aligned in BioEdit to a subtype C acute (Ͻ3-month) consensus sequence, which was generated from available CAPRISA 002 plasma Env sequences (n ϭ 592).…”
Section: Methodsmentioning
confidence: 99%